Hi sir!!

Asked by dhairya | 15th Jun, 2009, 03:47: PM

Expert Answer:

Let the forst term of the A.P. is a and the common diff be d

So the nth term of the A.P. is

nth term =a+[(n-1)d]

so

 the mth term is

mth term =a+[(m-1)d]

acc to question,

 m times the mth term = n times the nth term

So, we have

m[a+(m-1)d]=n[a+(n-1)d]

this gives

a[m-n] +d[m(m-1)-n(n-1)]=0

i.e.

remember we have assumed that m is not equal to n, so the factor m-n is not equal to zero. Hence the answer.

Answered by  | 15th Jun, 2009, 07:24: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.